The modern agricultural technology as an imperative to achieve the food security and well-being in Algeria amid the global developments - Bouchenaf Faiza (Journal of North African Economies, 2025)
The topic of this study raises the issue of achieving the food security. In this line, the last crises and the increase of the demand on food worldwide pushed many states, including Algeria, to adopt many agricultural developmental policies through supporting, encouraging, and reinforcing technology in the agricultural field as a fatal mechanism to achieve the food security Based on what was said, we used the descriptive analytical method and found out that the radical solution for a sustainable food security in Algeria is increasing and improving the productive capacity of the crops through the orientation towards the smart agriculture that depends mainly on the modern technological tools and the Artificial Intelligence systems.